An overview on personalisation of radiotherapy prescriptions in locally advanced non-small cell lung cancer: Are we there yet?. Issue 3 (September 2018) - Barrett, Sarah; Hanna, Gerard G.; Marignol, Laure
Abstract: Standard of care radiotherapy in LA-NSCLC is 60–66 Gy in 30–33 fractions. However outcomes for these patients are poor with 5-year survival in the range of 10–20%. Randomised controlled trials have shown that dose escalation in a linear fashion does not improve outcomes for all patients, thus there is a need to tailor the prescription to the individual patient. This review assesses the strategies published to personalise the radiation therapy dose prescription in LA-NSCLC. A systematic and scoping search of the literature was performed to identify studies that met the inclusion criteria. 19 relevant studies were identified ranging from prospective clinical trials to mathematically modelled concept studies. Heterogeneity existed between all clinical studies. Nine heterogeneous publications proposed methodology to adapt the dose prescription to the individual patient. A number of encouraging strategies have been identified but fall short of the evidence level required to influence clinical practice.